2015
DOI: 10.1177/0310057x1504300516
|View full text |Cite
|
Sign up to set email alerts
|

Revalidation: Implications for Australian Anaesthetists

Abstract: In early 2015, the Medical Board of Australia commissioned research into international revalidation models and what might be applicable for Australia. This review examines the implications for Australian anaesthetists. What problem is revalidation seeking to address? What is happening in similar countries? Is there an issue with Australian anaesthetists' performance? Isn't continuing professional development enough? Could the Medical Board target known high-risk doctors? What is the evidence for the benefit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Countries and regions like the United States, England, Canada, Australia, New Zealand and the European Union, have been on a long journey towards recertification or revalidation. Although the process is not mandatory in some of those countries, healthcare providers, i.e., healthcare institutions, end up requiring it from their practitioners (7).…”
Section: Why Scare Targets Recertification?mentioning
confidence: 99%
“…Countries and regions like the United States, England, Canada, Australia, New Zealand and the European Union, have been on a long journey towards recertification or revalidation. Although the process is not mandatory in some of those countries, healthcare providers, i.e., healthcare institutions, end up requiring it from their practitioners (7).…”
Section: Why Scare Targets Recertification?mentioning
confidence: 99%
“…There is convincing evidence regarding the positive effects of CPD activities on performance, and subsequent patient outcomes. Data from the U.S. indicates that board‐certified physicians have a lower likelihood of disciplinary proceedings and, correspondingly, performance on board examinations correlates positively with quality in care 7 . Whilst for anesthesiologists, it has been shown that patients in the care of a board‐certified practitioner have a lower 30‐day mortality than patients cared for by their non‐certified peers 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Roberts 1 provides us with a balanced and timely review of the existing processes that are utilised in comparable countries to determine and demonstrate 'fitness to practise' for doctors.…”
mentioning
confidence: 99%
“…The Medical Board of Australia, in the 'conversation' begun in 2012 2 , has specifically chosen to use the term 'revalidation' as distinct from 'recertification' or 'appraisal' 3 . 'Revalidation' in its most complex iteration is the process used in the United Kingdom (UK) by the General Medical Council (GMC) to determine 'fitness to practise' utilising the four domains described in its Good Medical Practice document as its metric 1 . When announcing the Collaboration for the Advancement of Medical Education, Research and Assessment research, the President of the Medical Board of Australia, Dr Joanna Flynn, made the following comment: "Commissioning this research will help make sure that the decisions the Board makes in future about revalidation are effective, evidence-based and practical" 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation